A Study of Mental Health Literacy Among North Korean Refugees in South Korea - Jin-Won Noh; Young Dae Kwon; Sieun Yu; Hyunchun Park; Jong-Min Woo (Korean Society for Preventive Medicine, 2015)
Objectives: This study aimed to investigate North Korean refugees' knowledge of mental illnesses and treatments and analyze the factors affecting this knowledge. Methods: Subjects were selected via a snowball sampling method, and the survey outcomes of 152 North Korean refugee participants were analyzed. The factors affecting knowledge of mental illnesses were analyzed via a regression analysis by constructing a multivariate model with mental illness knowledge score as the dependent variable. Results: The North Korean refugees' mental illness scores ranged from 3 to 24 points, with an average score of 13.0. Regarding the factors that influence mental illness knowledge, the subjects with South Korean spouses and those who had spent more time in South Korea had higher knowledge scores. Furthermore, the subjects who considered the mental health of North Korean refugees to be a serious issue revealed lower knowledge scores than those who did not believe it was a serious issue. The subjects who visit psychiatric clinics showed higher knowledge scores than those who do not. The South Korean subjects who had at least a college education exhibited higher scores than did those without advanced education. The subjects who are satisfied with life in South Korea manifested a higher mental illness knowledge score than those who are not. Conclusions: This study is significant as being the first study to ever measure and evaluate the level of North Korean refugees' knowledge of mental illnesses. In addition, the evaluations of North Korean refugees' mental illness knowledge and influencing factors while residing in South Korea created basic data that formed the foundation of an effort to enhance mental health literacy and provide proper mental health services. The results of this study can be utilized to solve mental health problems that might frequently occur during the unification process of North and South Korea in the future.